1999
DOI: 10.1159/000014146
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Intestinal Trefoil Factor in Developing Rat Intestine

Abstract: Intestinal trefoil factor (ITF or TFF3), a small peptide secreted at the mucosal surface by goblet cells throughout the mature intestine, appears to play important roles in the maintenance and repair of the intestinal mucosal barrier. To study the expression of TFF3 during development, intestinal tissues were collected from rats at different development stages and examined by Northern blot analysis, Western blot analysis and immunohistochemical staining for TFF3 mRNA and protein expression. The results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…An upregulated expression of TFF3 around the weaning period was measured in rat intestine [44]. This is concordant with our results in piglets, showing a 2-fold increased TFF3 expression in distal jejunum and ileum comparing specific pre-and postweaning time points.…”
Section: Discussionsupporting
confidence: 91%
“…An upregulated expression of TFF3 around the weaning period was measured in rat intestine [44]. This is concordant with our results in piglets, showing a 2-fold increased TFF3 expression in distal jejunum and ileum comparing specific pre-and postweaning time points.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we provide evidence to suggest that D12 may be a critical period as striking changes occurred with regard to the gene expression of mucins and Tff3 in the proximal and distal colon of normal pups. After weaning, we found a sharp increase in the mRNA and protein expression of Muc2, Muc4, and Tff3 in the proximal colon of normal rat, as previously observed (28,34,35). These changes in the expression of mucus constituents were parallel to morphologic changes of the mucosa (increase in crypt depth and in the number of goblet cells per crypt, reduction in the percentage of crypts in fission) that were consistent with previous studies (36 -38) and revealed a maturation of rat colonic mucosa.…”
Section: Discussionsupporting
confidence: 87%
“…5b). Tff3 protein is known to be secreted from goblet cells, where it is cotranslationally packaged with mucin (Lin et al, 1999). No immunoreactivity for Tff3 was observed at E13.5 and 15.5.…”
Section: Validation Of Microarray Resultsmentioning
confidence: 97%